Beyond (But Including) the CEO: Diffusing Corporate Social Responsibility throughout the Organization through Social Networks. (September 2014) - Jacobson, Kathryn J. L.; Hood, Jacqueline N.; Van Buren, Harry J.
Abstract Chief Executive Officers and other organizational leaders can affect how corporate social responsibility initiatives are perceived in their organizations. However, in order to be successful with regard to promoting CSR, leaders need to have strong network competencies and to move beyond charismatic leadership. In this paper we offer a critique of charismatic leadership as it relates to CSR, posit that the intellectual stimulation brought about by transformational leadership is more important in this regard, propose that internal and networking is a leadership competence highly relevant to CSR, and emphasize the importance of working through highly credible opinion leaders in promoting CSR.